DIPLOMASI KEBUDAYAAN JEPANG DI INDONESIA MELALUI ANIME FESTIVAL ASIA INDONESIA (AFAID) - Riri Ayu Novita; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes how Japan's cultural diplomacy through Anime Festival Asia utilizes the power of soft power. Japan, which experienced defeat after World War II, changed the image of their country, which no longer uses hard power but rather uses soft power to build relations with other countries through the spread of popular culture. The purpose of this study is to see how Japan's efforts to carry out cultural diplomacy through the Anime Festival Asia event in Indonesia. This study uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, websites. This research uses Constructivism perspective and Cultural Diplomacy theory. The results of this paper indicate that Japan as a country has succeeded in building better cooperation using Soft Diplomacy in a cultural context, through the spread of Japanese pop culture which is in demand by teenagers in Indonesia. This success can be seen at the Anime Festival Asia Indonesia (AFAID) which is the largest Japanese pop culture event in Indonesia, this activity shows success and benefits for both countries. Keywords: soft diplomacy, Popular Culture, Anime Festival Asia, Indonesia.